Treating binge eating and food addiction symptoms with low-carbohydrate Ketogenic diets: a case series - Matthew Carmen; Debra Lynn Safer; Laura R. Saslow; Tro Kalayjian; Ashley E. Mason; Eric C. Westman; Shebani Sethi (Journal of Eating Disorders, 2020)
Abstract Background Many patients with obesity and comorbid binge eating symptoms present with the desire to lose weight. Although some studies suggest that dietary restriction can exacerbate binge eating, others show dietary restriction is associated with significant reductions in binge eating. The effect of a particular type of dieting on binge eating, the ketogenic diet (a high fat, moderate protein, very low carbohydrate diet), is not known. Case presentations We report on the feasibility of a low-carbohydrate ketogenic diet initiated by three patients (age 54, 34, and 63) with obesity (average BMI 43.5 kg/m2) with comorbid binge eating and food addiction symptoms. All patients tolerated following the ketogenic diet (macronutrient proportion 10% carbohydrate, 30% protein, and 60% fat; at least 5040 kJ) for the prescribed period (e.g., 6–7 months) and none reported any major adverse effects. Patients reported significant reductions in binge eating episodes and food addiction symptoms including cravings and lack of control as measured by the Binge-Eating Scale, Yale Food Addiction Scale, or Yale-Brown Obsessive-Compulsive Scale modified for Binge Eating, depending on the case. Additionally, the patients lost a range of 10–24% of their body weight. Participants reported maintenance of treatment gains (with respect to weight, binge eating, and food addiction symptoms) to date of up to 9–17 months after initiation and continued adherence to diet. Conclusions Although the absence of control cases precludes conclusions regarding the specific role of ketogenic diets versus other forms of dietary restriction, this is the first report to demonstrate the feasibility of prescribing a ketogenic diet for patients with obesity who report binge eating and food addiction symptoms. Further research should seek to reproduce the observed effects in controlled trials as well as to explore potential etiologies.